Kratom, an Emerging Drug of Abuse, Raises Prolactin and Causes Secondary Hypogonadism: Case Report. (14th March 2018) - LaBryer, Lauren; Sharma, Rohan; Chaudhari, Kaustubh Suresh; Talsania, Mitali; Scofield, Robert Hal
Background. Kratom is a drug derived from the leaves of the tree Mitragyna speciose, which is native to southern Thailand. The route of administration is oral. Kratom has become increasingly available in the United States. The active ingredients in the drug bind the opioid mu-receptor; therefore, kratom has similar physiological effects as mu-opioids. Elevated prolactin is a common medical condition frequently caused by a variety drugs, including opioids. Case Report. A 42-year-old man presented with poor energy and low libido. He had mildly elevated serum prolactin with hypogonadotropic hypogonadism as evidenced by low serum testosterone with luteinizing hormone and follicle-stimulating hormone in the normal range. At his initial visit, he reported no use of any recreational or therapeutic drug. Two months later when seen in follow-up, both the testosterone and prolactin levels had returned to normal. At that visit he reported frequent use of kratom, which he had discontinued a few days after the first visit. Discussion . Kratom is now widely available in health food stores and online and is considered an emerging drug of abuse. At present kratom is legal in the United States, but recently the Drug Enforcement Administration served noticed of its intention of making kratom a Schedule I drug. A number of adverse events or side effects have been reported, but this is the first report of hyperprolactinemia as the result of ingestion of kratom.